A second Aleurodicinae from the Eocene Baltic amber—Medocellodes blackmani gen. et sp. nov. (Hemiptera, Sternorrhyncha, Aleyrodidae) - Drohojowska, Jowita; Tomanek, Natalia; Gröhn, Carsten; Szwedo, Jacek (Zootaxa, 2022)
A new genus and species of Aleurodicinae whiteflies from the Eocene Baltic amber is described. Medocellodes blackmani Drohojowska et Szwedo gen. et sp. nov. is the second representative of Aleurodicinae from Baltic amber, presenting mixture of plesiomorphic characters, as retention of median ocellus, with apomorphic states, shared also with other contemporaneous Aleurodicinae from Rovno amber. Morphological characters of the newly described fossil are briefly discussed.